Bubble Carbon-nanofibers Decorated with MnO2 Nanosheets as High-Performance Supercapacitor Electrode. (20th December 2016) - Zhao, Haitao; Han, Weihua; Lan, Wei; Zhou, Jinyuan; Zhang, Zemin; Fu, Wenbin; Xie, Erqing
Graphical abstract: Abstract: In this work, we have successfully prepared carbon-nanofibers with stringed in nanobubbles, as so-called bubble carbon-nanofibers (B-CNFs). The B-CNFs were obtained by exploding polyacrilonitrile (PAN) nanofibers with embedded ZnO nanoparticles as "bombs" during carbonization process at a temperature of 1000 °C. Benefiting from the easy electron transport path and high specific surface area, the B-CNFs show a high specific capacitance of 428 F g −1 at 1 A g −1 after decorated with MnO2 nanosheets, which is significantly superior to carbon fibers (CNFs)/MnO2 (203 F g −1 ) in the same situation. Moreover, it exhibits an excellent cycling stability with about 98.8% of the initial specific capacitance maintained after 1500 test cycles. This study provides an effective strategy to fabricate porous carbon nanomaterials as well as improve the capacitive performance of carbon-based supercapacitors.